Economic Analysis of Bio-Diesel for Agriculture Purpose of Indonesian Farm - Muhammad Bismadver Budiman; Karsten Wehner; Steffen Loest (Institut Teknologi Sepuluh Nopember, 2019)
Based on the 2015 annual energy forecast from Indonesia’s Agency for the Assessment and Application of Technology (BPPT), if present trends in energy usage continue unaltered, transport fuel consumption in Indonesia will increase on average almost 5% per year through 2050. Currently, liquid fossil fuel accounts for around 35% of Indonesia’s energy demand across all sectors. From various renewable energy and possible alternative fuels to replace the consumption of fossil fuels, biodiesel is projected to have potential to be developed regarding to the simple production process and affordable feed stocks. Biodiesel, as diesel engine fuel alternative, receives more attention among many feasible options. Biodiesel as one of the renewable energies, biodegradable and nontoxic fuel is expected to be one of the solutions. With the affordable feed stocks that can be obtained from various organic source like vegetable oils or animal fats and also the simple production, From the discussion of this Bachelor Thesis, the economic feasibility, necessary equipment and the time of storage of the biodiesel will be analyzed for biodiesel production plant including investment cost of making the biodiesel production plant by calculating the capital cost and the operational cost of a 5000-ton annual capacity of biodiesel. The purpose of this study is to analyze the investment of the biodiesel production facility by using a feasibility study method by using four parameters of economic feasibility study namely Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and the Profitability Index (PI) for assessing the Investment. Th result obtained is that the biodiesel production facility with the annual production of 5000 ton of biodiesel is feasible